Amino acids as copper corrosion inhibitors: A density functional theory approach - Kumar D.; Jain N.; Jain V.; Rai B. (My University, 2025)
Density functional theory was employed to investigate the corrosion inhibition mechanisms of four amino acids, viz. glutamic acid, cysteine, glycine, and their derivative glutathione. Quantum chemical descriptors such as highest occupied molecular orbital (HOMO) energy, lowest unoccupied molecular orbital (LUMO) energy, and energy gap (ΔEgap) were calculated to establish the relationship between the descriptors and corrosion inhibition efficiency. Further, in order to understand the adsorption mechanisms of amino acids with the copper surface, detailed adsorption studies were performed on Cu (1 1 1), Cu (1 0 0) and Cu (1 1 0) surfaces. The computed quantum chemical descriptors and the adsorption energies successfully predict the experimental inhibition efficiency trends. The optimized structures show formation of chemical bonds between the O, S, and N-atoms of the molecules and Cu (1 1 1) surface, confirmed by electron density difference and projected density of states plots Besides, the trends in computed adsorption energy were found to be unaffected by surface coverage studied by adsorbing multiple molecules (1–3) on Cu (1 1 1) surface. © 2020 Elsevier B.V.